Zdolność adaptacyjna narządu wzroku i czynniki ją zaburzające - Janosik, Elżbieta (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The aim of this article was to discuss one of the attributes of the sight organ – the eye adaptation capacity to the various light conditions and to provide the factors, that may cause disorders of this visual function course. The article presents the definition and physiological mechanism of eye adaptation. The dependence of adaptation course on existing light conditions (distinguishing dark and light adaptation and taking into account the glare phenomenon) was discussed. Possible, clinical reasons of deterioration of eye adaptation capacity were also listed. In conclusion, the possibility to use the examination of eye adaptation capacity in diagnosis (e.g. to state or monitor the development level of eye diseases and some of systemic diseases) or certification (e.g. to certify occupational usefulness) was emphasized.